Financial Stability and Prospects for the Development of Electricity Companies of the Russian Federation under Economic Uncertainty - Savchina, Oksana V.; Pavlinov, Dmitriy A.; Savchina, Olga V.; Al Humssi, Ahmad S.; Noga, Vladyslava I. (International Journal of Energy Economics and Policy, 2025)
The electricity sector plays an important role in a country’s economy due to its cross-sectoral importance. Economically, the industry is less vulnerable during the times of the economic uncertainty, as it is largely state supported. Electricity consumption and electricity generation have grown steadily over 1990-2023, with China, USA, India, Russia, Japan, Brazil, Canada, South Korea, Germany and France being the world market leaders. This article analyzes the current state and the main development trends of the electricity industry of the Russian Federation, as well as the financial stability of its companies. The analysis of the financial stability of PJSC Inter RAO and PJSC Rushydro, two electricity generating giants in the Russian Federation, has shown that they both remain financially healthy, however the increase of debt and the decrease of liquidity in the past five years have been of harm. Overall, electricity companies should not suffer much from the current economic uncertainty, as forecasts of the level of revenue show that Inter RAO should witness a 23.2% and 3.2% increase in 2025-2026, while Rushydro will have stable revenue levels by the end of 2026.